Social Media Based Marketing Model to Improve School Reputation - Ambarwati, Naumi; Bambang Ismanto; Sophia Tri Setyawati (Universitas Pendidikan Ganesha, 2023)
The non-optimal implementation of school promotions, as well as the lack of interactive social media-based school marketing models and guidelines, have an impact on the school's poor reputation. This research aims to develop an interactive social media-based marketing model to improve the school's reputation. This type of research is development research using mixed methods. The development model used is Borg and Gall. Product validation was carried out by 2 IT experts and two management experts. The product trial subjects are teachers, employees, students and parents. Data collection methods include interviews, document studies, questionnaires, observations and focus group discussions. Data collection instrument with questionnaire sheet. Data analysis techniques use qualitative and quantitative descriptive analysis. Process the model effectiveness trial data using the T-test on SPSS 21. The results of the research are the development of a marketing model with IT expert validation of 78% in the very feasible category. Assessment from management experts 90% is a very worthy category. The results of trials on research subjects regarding the model and guidelines for its use averaged 92% in the very feasible category. The product effectiveness test stated that treatment influenced the results in the experimental group. It was concluded that the social media-based marketing model and marketing guidebook